Adaptive Responses of Citrus grandis Leaves to Copper Toxicity Revealed by RNA-Seq and Physiology - Fenglin Wu (MDPI AG, 2021)
Copper (Cu)-toxic effects on Citrus grandis growth and Cu uptake, as well as gene expression and physiological parameters in leaves were investigated. Using RNA-Seq, 715 upregulated and 573 downregulated genes were identified in leaves of C. grandis seedlings exposed to Cu-toxicity (LCGSEC). Cu-toxicity altered the expression of 52 genes related to cell wall metabolism, thus impairing cell wall metabolism and lowering leaf growth. Cu-toxicity downregulated the expression of photosynthetic electron transport-related genes, thus reducing CO2 assimilation. Some genes involved in thermal energy dissipation, photorespiration, reactive oxygen species scavenging and cell redox homeostasis and some antioxidants (reduced glutathione, phytochelatins, metallothioneins, l-tryptophan and total phenolics) were upregulated in LCGSEC, but they could not protect LCGSEC from oxidative damage. Several adaptive responses might occur in LCGSEC. LCGSEC displayed both enhanced capacities to maintain homeostasis of Cu via reducing Cu uptake by leaves and preventing release of vacuolar Cu into the cytoplasm, and to improve internal detoxification of Cu by accumulating Cu chelators (lignin, reduced glutathione, phytochelatins, metallothioneins, l-tryptophan and total phenolics). The capacities to maintain both energy homeostasis and Ca homeostasis might be upregulated in LCGSEC. Cu-toxicity increased abscisates (auxins) level, thus stimulating stomatal closure and lowering water loss (enhancing water use efficiency and photosynthesis).